AI Driven Smart Surveillance System with Motion Detection - Ganesh Sonawane; Sayali Sanap; Shrutika Dhawade; Prof. Vyavahare V. A.; Dr. Divekar S. N. (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The integration of advanced deep learning technologies into criminal activity detection systems has revolutionized public safety and surveillance mechanisms. This review paper delves into the state-of-the-art methodologies employed in optimized systems for detecting criminal activities, emphasizing facial recognition, video surveillance, and weapon detection. These systems achieve real-time processing, high accuracy, and scalability. Key challenges, including dataset biases, computational inefficiencies, and ethical concerns, are critically analyzed, with potential solutions and emerging trends highlighted. This review aims to provide a holistic understanding of the technological advancements, practical applications, and future directions in criminal activity detection using artificial intelligence.